EFISIENSI PERSEDIAAN THRIFT STORE DI TARAKAN DENGAN METODE JIT, EOQ DAN SAFETY STOCK - Hidayat, Nurul; Fatma Azzahra, Yazmenita Kayla; Mastura, Nuralia; Rahmadani, Nova (Transpublika Publisher, 2024)
This study aims to optimize fashion product inventory at the Romagirlkaltara thrift store in Tarakan using the Just in Time (JIT) approach. The JIT method is applied to reduce inventory costs and improve inventory efficiency by adjusting stock levels based on daily demand and optimizing restocking frequency. The findings indicate a 31.25% reduction in inventory costs, from Rp12,000,000 to Rp8,250,000 per period. The implementation of JIT has proven effective in helping the store align inventory with fluctuating market demand, thereby reducing the risk of overstock and enhancing cash flow. These findings underscore the relevance of JIT in inventory management, particularly for thrift fashion businesses that are highly influenced by dynamic consumer trends and preferences.